2022
DOI: 10.1021/jacs.1c12398
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer Structure Manipulation of Iron Oxychloride by Potassium Cation Intercalation to Steer H2O2 Activation Pathway

Abstract: Structural regulation of the active centers is often pivotal in controlling the catalytic functions, especially in iron-based oxidation systems. Here, we discovered a significantly altered catalytic oxidation pathway via a simple cation intercalation into a layered iron oxychloride (FeOCl) scaffold. Upon intercalation of FeOCl with potassium iodide (KI), a new stable phase of K +intercalated FeOCl (K-FeOCl) was formed with slided layers, distorted coordination, and formed high-spin Fe(II) species compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 45 publications
(65 reference statements)
1
43
0
Order By: Relevance
“…The possible role of Fe IV O was first considered because it has been reported to be formed in the Fhy/H 2 O 2 system at pH = 4.0 and could extract electrons from organic molecues. , To verify this, PMSO was used as the quenching agent for Fe IV O ( k PMSO,Fe(IV) = 1.23 × 10 5 M –1 s –1 ). , In case when Fe IV O is the main active species for the oxidation of 4-HBA, the presence of excessive PMSO could effectively inhibit the removal of 4-HBA. However, Figure S11 shows that the degradation of 4-HBA (100 μM) is not affected by the excessive PMSO (1 and 10 mM).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The possible role of Fe IV O was first considered because it has been reported to be formed in the Fhy/H 2 O 2 system at pH = 4.0 and could extract electrons from organic molecues. , To verify this, PMSO was used as the quenching agent for Fe IV O ( k PMSO,Fe(IV) = 1.23 × 10 5 M –1 s –1 ). , In case when Fe IV O is the main active species for the oxidation of 4-HBA, the presence of excessive PMSO could effectively inhibit the removal of 4-HBA. However, Figure S11 shows that the degradation of 4-HBA (100 μM) is not affected by the excessive PMSO (1 and 10 mM).…”
Section: Resultsmentioning
confidence: 99%
“…3.0) and formation of iron sludge that interrupts the Fe­(II)/Fe­(III) catalytic cycle. Consequently, tremendous efforts have been devoted to developing various heterogeneous Fenton systems that overcome the abovementioned limitations. Compared to the homogeneous version, the heterogeneous Fenton reaction involves complicated solid–liquid interface processes and mechanisms. Elucidating the oxidation mechanism and degradation pathway of organic pollutants in these systems is of paramount importance, not only for a deeper understanding from a fundamental perspective but also for the design of more efficient heterogeneous Fenton systems from a practical perspective. A well-accepted protocol is to examine the nature of the reactive species (e.g., HO · , high-valent metal-oxo species) that are derived from the heterogeneous metal–H 2 O 2 complex (M–OOH, M is the active metal site) ,, and then to evaluate the contribution of each reactive species to the degradation of one or several specific compounds, assuming that the activation of H 2 O 2 and the subsequent pollutant degradation are separate processes. , Some recent studies on other advanced oxidation processes have indicated that when the organic compounds are able to form strong interaction with the catalyst, both processes, i.e., the oxidant activation and the pollutant degradation, might entangle with each other, resulting in more abundant oxidation mechanisms and degradation pathways of the target molecules. , However, such a possible role of the interaction between the organic compounds and the catalyst in the oxidation mechanism/pathway has been scarcely considered in classic H 2 O 2 -based heterogeneous Fenton systems. The elucidation of the mechanisms involved in the heterogeneous Fenton reaction that considers the interaction between the pollutant and the catalyst could better reflect the real water treatment scenarios in which the pollutants are diverse in molecular structures, some of which could form strong interaction with the catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] Herein, we focus our attention on layered metal oxyhalide MOX (M = Fe, Bi; X = Cl, Br, I), whose heterogeneous structure with alternating [M 2 O 2 ] 2+ and halogen layers might enable the presence of electron-donor and -acceptor units in a confined region. [23][24][25][26] Although halogens are considered to be robust nucleophilic species for attacking electrophilic carbon atom of epoxy ring, the halogen-terminated surface of MOX would inhibit the exposure of metal atoms serving as electron-acceptor units. Additionally, halogen atom (Br, Cl, I) existing in the crystal lattice would be advantageous for catalyst recovery and separation.…”
Section: Introductionmentioning
confidence: 99%
“…Layered iron oxychloride with abundant elemental resource has been applied to energy and catalysis fields, [1,2] for its high theoretical capacity and high production of the OH radicals. The chloride ion battery (CIB) with nearly 2500 Wh L −1 theoretical energy density and abundant material resources, has been viewed as a promising anionic battery [3,4] .…”
Section: Introductionmentioning
confidence: 99%